2009
DOI: 10.1007/s12665-009-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Earth fissures in Jiangsu Province, China and geological investigation of Hetang earth fissure

Abstract: Earth fissures are a geohazard in Jiangsu Province, China. They can be caused by earthquakes and active faults, underground mining, groundwater extraction and landslides. In order to establish a provincial rehabilitation plan in Jiangsu, a range of monitoring programs, surveys, geological investigations and modeling have been implemented or planned. One of the focuses of the project is the land subsidence and earth fissures caused by excessive groundwater withdrawal in Suzhou, Wuxi and Changzhou (Su-Xi-Chang) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…In terms of their mechanical characteristics, the majority of fissures are tensile, while some are shearing in form. In the trench excavation of an earth fissure in the SXC area, a shear zone 20-50 mm wide was clearly observed (Wang et al 2010). The occurrence of earth fissures in the SXC area is temporally and spatially related to the extraction of groundwater.…”
Section: Characteristics Of Earth Fissuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of their mechanical characteristics, the majority of fissures are tensile, while some are shearing in form. In the trench excavation of an earth fissure in the SXC area, a shear zone 20-50 mm wide was clearly observed (Wang et al 2010). The occurrence of earth fissures in the SXC area is temporally and spatially related to the extraction of groundwater.…”
Section: Characteristics Of Earth Fissuresmentioning
confidence: 99%
“…The horizontal seepage force causes the soil particle grains in an aquifer to move horizontally, and differential horizontal displacement in the soil may lead to tensile cracks in aquifers, which can propagate upwards. However, this model could not explain earth fissures with distinct shear strains (Wang et al 2010). On the basis of the Mohr-Coulomb failure criterion, Budhu (2008) proposed that earth fissures in aquifer alluvium are caused by simple shear stress on vertical planes and rotation, while earth fissures in upper cemented alluvium are induced by simple shear strain and rotation due to differential settlement of aquifer alluvium.…”
Section: Introductionmentioning
confidence: 97%
“…Liu et al (2004) identified the factors related to the development of earth fissure including bedrock hills, buried terraces, Karst collapse, structural differences of the aquifer system, and overexploitation of groundwater. Wang et al (2009Wang et al ( , 2010 reported earth fissures triggered by excessive groundwater withdrawal and the variability of bedrock depth in Hetang town, Jiangyin City. Yu et al (2006) analyzed the mechanisms leading to occurrence of some typical earth fissures using three-dimensional seismic exploration techniques.…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS dynamic responses, earth fissure, RC frame structure, seismic design, seismic performance, shaking table test 1 | INTRODUCTION Geological disasters of earth fissures occurred in many countries around the world, such as China, America, Greece, Myanmar, Mexico, and Turkey. [1][2][3][4][5][6][7][8] It is commonly known that the earth fissure hazards are caused by excessive exploitation of underground water and other tectonization activities such as earthquakes. [9][10][11][12] These earth fissures lead to damages of the buildings, farmland destruction, road deformation, and pipeline rupture, which seriously affected people's lives, factory production, and safety.…”
Section: Discussionmentioning
confidence: 99%